Risk and markers of severe acute pancreatitis - Papachristou, Georgios I; Clermont, Gilles; Sharma, Arun; Yadav, Dhiraj; Whitcomb, David C (Gastroenterology clinics of North America, 2007)
Acute pancreatitis begins with pancreatic injury, elicits an acute inflammatory response, and encompasses a variety of potential complications in a subset of patients. Early determination of severity and risk of complications is crucial for instituting immediate interventions to improve outcome. The severity of acute pancreatitis is a function of the amount of pancreas that is injured and the intensity of the inflammatory response. Early death is mainly linked to an overwhelming inflammatory response leading to cardiovascular collapse or acute respiratory distress syndrome, whereas late death is associated with infected pancreatic necrosis and sepsis. This article reviews recent advancements in understanding the pathogenesis, immunology, and genetics of severe acute pancreatitis, and the literature on laboratory-based markers, which predict a severe clinical course and pancreatic necrosis.